On the Structures of Abelian π-Regular Rings - Jianwei Lu; Liguo He (International Journal of Mathematics and Mathematical Sciences)
Assume that R is an Abelian ring. In this paper, we characterize the structure of R whenever R is π-regular. It is also proved that an Abelian π-regular ring is isomorphic to the subdirect sum of some metadivision rings.